A Review of the Routledge Handbook on Smuggling. Issue 1 (28th September 2022) - Bish, Alexandre
The literature on smuggling is progressing steadily as the topic has received increasing attention in recent years. However, research has developed across several fields and in a disjointed fashion. This book review reflects upon a recent publication, which attempts to consolidate smuggling research: The Routledge Handbook on Smuggling (Gallien and Weigand, 2021). The book helps lay the foundations for the conceptualisation of smuggling and provides clear guidance for its study, establishing it as a key reference tool for both neophyte and veteran researchers alike.